2012
DOI: 10.2215/cjn.04760511
|View full text |Cite
|
Sign up to set email alerts
|

Ergocalciferol Supplementation in Children with CKD Delays the Onset of Secondary Hyperparathyroidism

Abstract: SummaryBackground and objectives Vitamin D deficiency is an important contributor to the development of hyperparathyroidism and is independently associated with cardiovascular and bone disease. The hypothesis was that nutritional vitamin D (ergocalciferol) supplementation in children with CKD stages 2-4 delays the onset of secondary hyperparathyroidism.Design, setting, participants, & measurements A randomized, double-blinded, placebo-controlled study in children with CKD2-4 who had 25-hydroxyvitamin D [25(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 38 publications
1
50
0
2
Order By: Relevance
“…There is no analogous study in healthy children. 60% of children with chronic kidney disease maintained 25OHD Ͼ 30 ng/mL while receiving 2,000 IU of daily vitamin D 2 (28). Our finding of a significantly lower rate of maintenance of serum 25OHD Ͼ 30 ng/mL could be explained by lower bioavailability of vitamin D 2 in subjects with IBD, even inactive (29).…”
Section: Discussionmentioning
confidence: 60%
“…There is no analogous study in healthy children. 60% of children with chronic kidney disease maintained 25OHD Ͼ 30 ng/mL while receiving 2,000 IU of daily vitamin D 2 (28). Our finding of a significantly lower rate of maintenance of serum 25OHD Ͼ 30 ng/mL could be explained by lower bioavailability of vitamin D 2 in subjects with IBD, even inactive (29).…”
Section: Discussionmentioning
confidence: 60%
“…It was consistent with the findings of Zisman et al [29] and Hari et al [30], who had stated that ergocalciferol/cholecalciferol supplementation for the management of hyperparathyroidism was more effective in the early stages of CKD. Similarly, Shroff et al reported better control of secondary hyperparathyroidism with ergocalciferol [31] Receptors for activated vitamin D spread along various types of cells, including osteoblasts, parathyroid cells, renal tubular epithelium and also lymphocytes, vascular smooth muscle, and myocardial cells [32]. 25OHD has been demonstrated to preserve cardiac function by preventing myocardial hypertrophy either by ameliorating iPTH secretion or acting via vitamin D-dependent mechanisms, suppression of vascular smooth muscle cell proliferation, and modulation of the RAAS [33].…”
Section: Discussionmentioning
confidence: 98%
“…A recent trial reported that ergocalciferol prevented sHPT in children with CKD stage ≥2. 80 As PTH levels remain relatively stable with eGFR values >60 mL/min/1.73 m 2 , a longer supplementation phase and follow-up period might be necessary in the adult CKD population to see a preventive effect of vitamin D prohormone on the development of sHPT.…”
Section: Vitamin D Prohormone Supplementation In Ckd Stages 3-5mentioning
confidence: 99%